Classification of Phonemes using Sound and Visual Information - Balbonas, D.; Daunys, G. (Elektronika ir Elektrotechnika, 2005)
The paper concerns automatic speech recognition using differential features of phonemes. The methods to obtain parameters for phonemes classification are discussed. The analysis of application visual information for speech recognition is done. The system for classification Lithuanian language visemes was proposed. The possibilities about combining sound and visual information for speech recognition is discussed. Ill. 3, bibl. 9 (in Lithuanian; summaries in Lithuanian, English and Russian).